(untitled) (Psychology Travelogs, 2025)
The article examines the theoretical and applied aspects of emotional burnout syndrome, social intelligence, critical thinking, and apperception among military personnel and specialists in socionomic professions. The study analyzes the functioning and interdependence of emotional, cognitive, and socio-communicative phenomena of personality. Based on an empirical investigation conducted among servicemen as well as psychologists, educators, social workers, and medical professionals, a relationship was established between emotional burnout, social intelligence, critical thinking, and apperception. It has been proven that well-developed cognitive-analytical, socio-communicative, and situational-behavioral skills contribute to reducing the level of emotional exhaustion, whereas increased subjectivity of perception and its dependence on previous experience raise the likelihood of developing emotional burnout syndrome. The conducted analysis of the mentioned phenomena and their interrelations contributes to a deeper understanding of the psychological mechanisms of personal adaptation and maladaptation, the development of effective measures for correcting psychological destructions and disorders, and the prevention of mental health deterioration. In particular, the results obtained may be used in the design and implementation of effective training programs for the correction and prevention of professional burnout and other psychological destructurations of personality.